Perfectionism and academic procrastination in students working on their thesis at University X in Medan City: The role of fear of failure as a mediator - Siregar, Hirmar Waki Omnihara; Millfayetty, Sri; Hasanuddin, Hasanuddin (Universitas Ahmad Dahlan, 2024)
Students face significant academic demands when completing their final projects, which often leads to feelings of reluctance and postponement to do the final project. This study aims to examine the role of fear of failure as a mediator in the relationship between perfectionism on the procrastination among students working on their theses. Employing a quantitative approach, this research utilizes a cross-sectional study method. The sampling technique applied in this study is cluster random sampling, involving a total of 358 participants from one of the universities in Medan City. The research instruments used include the APS-S scale, the multidimensional perfectionism scale, and the fear of failure scale. The results of mediation analysis using Structural Equation Modelling (SEM) with the PLS-SEM 3.0 program showed that fear of failure significantly mediated the influence of perfectionism on academic procrastination in students with t-Statistic= 8.866>1.96 and p-Values=0.000<0.05. These findings imply that fear of failure amplifies the tendency of perfectionist students to avoid situations that may lead to mistakes or failures, consequently resulting in delays in completing their theses. It is better for them to develop a growth mindset by shifting the focus from outcomes to the learning process and setting realistic goals will help students reduce academic procrastination.